In the form of a question : the joys and rewards of a curious life - Schneider, Amy, 1979- (Avid Reader Press, 2023)
"An inspirational and bold memoir from the most successful woman ever to compete on Jeopardy!--and an exploration of what it means to ask questions of the world and of yourself. ANSWER: Who Is Amy Schneider? In eighth grade, Amy was voted "Most likely to appear on Jeopardy!" by her classmates. Decades later, this trailblazer finally got her chance. Not only did she walk away with $1.3 million while captivating the world with her impressive forty-game winning streak, but she made history and won an even greater prize--the joy of being herself on national television and blazing a trail for openly queer and transgender people around the world. Now, she shares her singular journey that led to becoming an unlikely icon and hero to millions. Her super power: Boundless curiosity and fearless questioning. In the Form of a Question explores some of the innumerable topics that have fascinated Amy throughout her life--books and music, Tarot and astrology, popular culture and computers, sex and relationships--but they all share the same purpose: to illustrate, and celebrate, the results of a lifetime spent asking, why? "--